Video Modeling to Increase Pragmatics in Asperger's Syndrome - Farley, Gretta M. (My University, 2011)
Pragmatic skills prove difficult for children with Asperger’s syndrome. The purpose of this study was to determine if video modeling positively impacted pragmatic skills. The subject was a 9 year old with Asperger’s Syndrome. A spontaneous speech-language sample was conducted to gather data. The researcher and subject discussed the components of a conversation. A live TV interview of an author the subject was already interested in was viewed. The subject practiced and conducted his own interview with a partner who also had Asperger’s Syndrome. The partner had previously participated in a similar study. Four behaviors were targeted for increase or decrease. The intervention was successful in three of four behaviors resulting in an increase of pragmatic appropriateness overall.
Keywords: Asperger